Transparent tough plastic master batch and preparation method thereof
By using specific formulas and preparation methods of heat-resistant PMMA, toughener, lubricant and antioxidant in transparent plastic masterbatches, the shortcomings of existing transparent plastic masterbatches in toughness and heat resistance are solved, and transparent plastic masterbatches with high toughness and heat resistance are achieved, improving the stability and safety of the product.
Patent Information
- Application Number
- CN202411584311.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-07
- Publication Date
- 2025-03-11
AI Technical Summary
The existing transparent plastic masterbatches have shortcomings in toughness and heat resistance, and are prone to cracking or deforming under external impact and high temperature environments, affecting the service life and safety of the product.
A transparent tough plastic masterbatch including 75-85 parts of heat-resistant PMMA, 10-15 parts of toughener, 1-2 parts of lubricant and 1-2 parts of antioxidant is used to improve the toughness and heat resistance of the plastic through specific formulations and preparation methods.
It realizes the high toughness and heat resistance of transparent plastic masterbatch, and can maintain stability and performance under external impact and high temperature environments, extend the service life of the product and improve safety.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of plastics, and in particular to a transparent tough plastic masterbatch and a preparation method thereof. Background Art
[0002] In the plastic processing industry, plastic masterbatch is an important raw material, and its performance directly affects the quality and application range of the final plastic products. With the development of science and technology and the changes in market demand, the performance requirements for plastic products are getting higher and higher, especially for the toughness and heat resistance of transparent plastic products on the outer wall.
[0003] Traditional outer wall transparent plastic masterbatch is mainly composed of resin, filler, plasticizer, stabilizer, etc. Although these materials can meet certain processing and performance requirements, they are still insufficient in toughness and heat resistance. For example, some plastic products are prone to cracking or deformation when impacted by external forces, and are prone to softening or deformation in high temperature environments, thus affecting the service life and safety of the product.
[0004] Therefore, how to develop a transparent tough plastic masterbatch with good toughness and heat resistance is an urgent problem to be solved in the current plastic processing industry. Summary of the invention
[0005] The purpose of the present invention is to provide a transparent tough plastic masterbatch and a preparation method thereof, so as to solve the following technical problems:
[0006] How to improve the toughness and heat resistance of transparent tough plastic masterbatch.
[0007] The purpose of the present invention can be achieved through the following technical solutions:
[0008] In a first aspect, the present invention discloses a transparent tough plastic masterbatch, comprising the following raw materials in parts by weight: 75-85 parts of heat-resistant PMMA (polymethyl methacrylate), 10-15 parts of a toughening agent, 1-2 parts of a lubricant, and 1-2 parts of an antioxidant;
[0009] Preferably, the transparent tough plastic masterbatch comprises the following raw materials in parts by weight: 80 parts of heat-resistant PMMA, 12 parts of toughening agent, 1.5 parts of lubricant, and 1.5 parts of antioxidant;
[0010] Wherein, the heat-resistant PMMA comprises PMMA, bisphenol fluorene and bergamot lactone in a molar mass ratio of 1:X:(1-X), X=(0.5-0.7);
[0011] Preferably, X=0.6, that is, the heat-resistant PMMA comprises PMMA, bisphenol fluorene and bergamotolide in a molar mass ratio of 1:0.6:0.4.
[0012] Furthermore, the preparation method of the heat-resistant PMMA is:
[0013] The first step is to add PMMA, bisphenol fluorene and bergamot lactone into the solvent according to the molar mass ratio and mix them evenly to form a mixed solution with a solid content of about 50%, then add a catalyst, stir at 140° C. for 4 hours to make the system salt and remove a large amount of water, then heat to 160° C. and stir for 1 hour to remove toluene, and finally heat to 200° C. for polymerization reaction for 6 hours to obtain a slurry;
[0014] Step 2: Add boiling water to the slurry and stir at a constant temperature for 12 hours to remove residual solvent and inorganic salts. After filtering and drying, dissolve in N-methylpyrrolidone and stir evenly to remove unreacted raw materials. After filtering, dissolve in anhydrous ethanol to obtain a flocculent precipitate. Finally, wash the flocculent precipitate with ethanol several times to remove the solvent. After filtering and drying, transparent heat-resistant PMMA is obtained.
[0015] In this process, PMMA, bisphenol A and bergamot lactone are first salified and then polycondensed. The salification process ensures the correct ratio between the monomers, forms a more stable intermediate, and prevents the occurrence of end-capping in the subsequent polycondensation process, which affects the molecular weight and performance of the polymer.
[0016] Bisphenol fluorene contains fluorenyl groups, and bergamot lactone contains a furan ring carbon skeleton structure. After the condensation reaction, the fluorenyl groups in bisphenol fluorene and the furan ring carbon skeleton structure in bergamot lactone are introduced into PMMA. The fluorenyl groups and the furan ring carbon skeleton structure hinder the close stacking of polymer molecular chains, destroying the regularity of the chain segments. Therefore, the molecular chain spacing of the obtained heat-resistant PMMA is increased, which is conducive to the entry of small molecule solvents, so it exhibits good solubility and fluidity.
[0017] At the same time, more importantly, the special skeleton structure of the fluorene group can enhance the rigidity of the molecular chain, inhibit the free movement of the molecular chain, and thus improve its thermal stability, thereby improving the heat resistance of PMMA.
[0018] Further, in the first step, the solvent is one of sulfolane, tetrahydrofuran, and dimethylformamide;
[0019] Preferably, the solvent is sulfolane.
[0020] Further, in the first step, the catalyst is one of anhydrous potassium carbonate, triphenylmethane, and tert-butyl hydroperoxide;
[0021] Preferably, the catalyst is anhydrous potassium carbonate.
[0022] Further, in the first step, the amount of the catalyst used in terms of molar mass is the same as the amount of PMMA used in terms of molar mass.
[0023] Furthermore, the toughening agent comprises glycidyl methacrylate and vinyl acrylate in a molar mass ratio of 1:1.
[0024] Furthermore, the preparation method of the toughening agent is:
[0025] The first step is to add glycidyl methacrylate and vinyl acrylate to a solvent according to the molar mass ratio and mix them evenly to form a mixed solution with a solid content of about 50%, then add an appropriate amount of initiator, stir at 230° C. for 30 minutes under nitrogen protection, cool to room temperature and filter to obtain a toughening agent precursor;
[0026] Preferably, the solvent is dimethylformamide or tetrahydrofuran, more preferably dimethylformamide;
[0027] Preferably, the initiator is benzoyl peroxide or azobisisobutyronitrile, more preferably benzoyl peroxide;
[0028] In the second step, the toughening agent precursor is distilled to remove the solvent and unreacted monomers. The distilled product is repeatedly washed and filtered with deionized water, and the obtained filter material is dried to obtain the toughening agent.
[0029] In this process, the epoxy group in glycidyl methacrylate and the carboxyl group in vinyl acrylate undergo an ester exchange reaction, so that glycidyl methacrylate and vinyl acrylate are connected. Since vinyl acrylate has excellent toughness and flexibility, after combining with glycidyl methacrylate, glycidyl methacrylate has excellent toughness.
[0030] Furthermore, the lubricant is pentaerythritol stearate.
[0031] Furthermore, the antioxidant is a compound type of antioxidant 1076 or antioxidant 168.
[0032] In a second aspect, the present invention further discloses a method for preparing the transparent tough plastic masterbatch as described above, comprising the following preparation steps:
[0033] S1. Weigh heat-resistant PMMA, toughening agent, lubricant and antioxidant according to weight ratio, add them into a high-speed mixer and mix them evenly to obtain a mixture;
[0034] S2: placing the mixed material in an extruder and extruding it at an increasing temperature of 80-100°C at the initial temperature and 200-220°C at the final temperature, and obtaining masterbatch particles after pelletizing;
[0035] S3. The obtained masterbatch particles are placed in a dryer and dried at 80° C. for 3 hours to obtain a transparent tough plastic masterbatch that can be packaged and stored.
[0036] In this process, PMMA in the heat-resistant PMMA and glycidyl methacrylate in the toughening agent have good melt miscibility, and the toughening agent can be grafted onto the heat-resistant PMMA to give it good toughness.
[0037] Beneficial effects of the present invention:
[0038] 1. In the transparent tough plastic masterbatch of the present invention, the main material heat-resistant PMMA introduces the fluorenyl group in bisphenol fluorene and the furan ring carbon skeleton structure in bergamot lactone. The fluorenyl group and the furan ring carbon skeleton structure hinder the close stacking of polymer molecular chains, so that the regularity of the chain segments is destroyed. Therefore, the molecular chain spacing of the obtained heat-resistant PMMA is increased, which is conducive to the entry of small molecule solvents, so it exhibits good solubility and fluidity; at the same time, more importantly, the special skeleton structure of the fluorenyl group can enhance the rigidity of the molecular chain, inhibit the free movement of the molecular chain, and thereby improve its thermal stability, so that the heat resistance of PMMA is improved.
[0039] 2. A self-made toughening agent is added to the transparent tough plastic masterbatch of the present invention. The epoxy group in the glycidyl methacrylate in the toughening agent and the carboxyl group in the vinyl acrylate connect the glycidyl methacrylate with the vinyl acrylate through an ester exchange reaction. Since the vinyl acrylate has excellent toughness and flexibility, the glycidyl methacrylate has excellent toughness after being combined with the glycidyl methacrylate. The PMMA in the heat-resistant PMMA and the glycidyl methacrylate in the toughening agent have good melt miscibility. The toughening agent can be grafted onto the heat-resistant PMMA to make it have good toughness. DETAILED DESCRIPTION
[0040] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0041] The experimental methods in the following examples, unless otherwise specified, are all conventional methods, and are performed according to the techniques or conditions described in the literature in the field or according to the product instructions. The materials, reagents, etc. used in the following examples, unless otherwise specified, can all be obtained from commercial channels.
[0042] Preparation Example 1
[0043] Preparation of heat-resistant PMMA.
[0044] Step 1: PMMA (1 mol, 102.1 g), bisphenol fluorene (0.6 mol, 210.25 g) and bergamot lactone (0.4 mol, 86.48 g) were added into a stirring tank containing 400 g of sulfolane solvent in a molar mass ratio of 1:0.6:0.4, and stirred evenly to form a mixed solution, 1 mol (138.21 g) of anhydrous potassium carbonate was added to the mixed solution, and stirred at 140°C and 300 rpm for 4 h, then heated to 160°C and stirred at 300 rpm for 1 h, and finally heated to 200°C and stirred for 6 h to obtain a slurry;
[0045] Step 2: Add 500g of waste water to the stirring tank containing the slurry, set the temperature of the stirring tank to 100℃ to maintain the temperature of boiling water, stir continuously at 200rpm for 12h at this temperature, then let it stand, cool to room temperature, transfer to the filter to filter, place the filter material in a vacuum drying oven and dry it at 120℃ for 2h, then transfer it to a stirring tank containing 300mL of N-methylpyrrolidone and stir it at 300rpm for 30min, transfer it to the filter to filter again, add the obtained filter material to a beaker containing 200mL of anhydrous ethanol and stir evenly, then let it stand to obtain a milky white flocculent precipitate, wash the flocculent precipitate repeatedly with anhydrous ethanol 3 times, and then transfer it to the filter to filter, transfer the obtained filter material to a vacuum drying oven and dry it at 120℃ for 6h to obtain transparent heat-resistant PMMA, which is weighed to be 397.67g.
[0046] Preparation Examples 2-3 and Comparative Examples 1-2
[0047] Preparation Examples 2-3 and Comparative Preparation Examples 1-2 are all used to prepare heat-resistant PMMA. The difference between the preparation methods and Preparation Example 1 is only that the amounts of PMMA, bisphenol fluorene and bergapten are different, and the other operating steps and conditions are exactly the same; the amounts of PMMA, bisphenol fluorene and bergapten in Preparation Examples 1-3 and Comparative Preparation Examples 1-2 are listed in Table 1, which is as follows:
[0048] Table 1
[0049]
[0050] Preparation Example 4
[0051] Preparation of toughening agent.
[0052] Step 1: add glycidyl methacrylate (1 moL, 142.14 g) and vinyl acrylate (1 moL, 100.12 g) in a molar ratio of 1:1 to 250 g of dimethylformamide solvent and stir at 300 rpm for 20 min, then add 50 g of benzoyl peroxide, stir at 230 ° C for 30 min under nitrogen protection, cool to room temperature and filter in a filter to obtain a filter material as a toughening agent precursor;
[0053] Step 2: The toughening agent precursor is transferred to an integrated distiller for distillation. The distilled product is repeatedly washed and filtered with deionized water for 3 times. The filter material is transferred to a vacuum drying oven and dried at 120°C for 4 hours to obtain the toughening agent. After weighing, the toughening agent is 240.99g.
[0054] Example 1
[0055] Preparation of transparent tough plastic masterbatch.
[0056] Step 1: Add 32 g of the heat-resistant PMMA prepared in Preparation Example 1, 4.8 g of the toughening agent prepared in Preparation Example 4, 0.6 g of pentaerythritol stearate, and 0.6 g of antioxidant 1076 into a high-speed mixer in a weight ratio of 80:12:1.5:1.5 and mix well;
[0057] Step 2: Set the temperature of the laboratory twin-screw extruder from zone 1 to zone 10 to 80°C, 180°C, 200°C, 210°C, 210°C, 200°C, 200°C, 210°C, 210°C, and 210°C, respectively, and set the die temperature to 220°C. After the temperature is stable for 40 minutes, place the mixed material in the twin-screw extruder for extrusion production, set the speed of the twin-screw extruder to 400rpm, the die pressure to 2MPa, and the vacuum degree to 0.5KPa, and obtain the masterbatch particles after pelletizing;
[0058] Step 3: Place the obtained masterbatch particles in a dryer and dry them at 80° C. for 3 hours to obtain a transparent tough plastic masterbatch that can be packaged and stored.
[0059] Example 2-3
[0060] Compared with Example 1, the only difference between Example 2-3 is that the amounts of the heat-resistant PMMA prepared in Preparation Example 1, the toughening agent prepared in Preparation Example 4, pentaerythritol stearate, and the antioxidant 1076 are different, and the other operation steps are exactly the same as the steps; the amounts of the raw materials in Examples 1-3 are listed in Table 2, which is as follows:
[0061] Table 2
[0062]
[0063] Comparative Example 1
[0064] Compared with Example 1, the only difference is that the heat-resistant PMMA prepared in Preparation Example 1 is replaced by ordinary PMMA, and the other operation steps are exactly the same as the steps; finally, a transparent plastic masterbatch is obtained.
[0065] The transparent tough plastic masterbatches prepared in Examples 1-3 and Comparative Example 1 were respectively made into plastic sheets for performance testing. The preparation method was: the masterbatch was injection molded at 160°C and 4MPa for 3min, then cured at 200°C for 2h, and then cured at 230°C and 260°C for 2h respectively to obtain a test piece with a length of 10cm, a width of 4cm, and a thickness of 0.5cm. The performance test method was as follows:
[0066] Mechanical properties: According to GB / T 9341-2008, the bending strength and tensile strength were measured at room temperature (25°C) and high temperature (200°C) using an electronic universal testing machine.
[0067] Heat resistance: According to GB / T 11205-2009, the thermal conductivity is measured by a thermal constant analyzer; the vertical combustion (UL-94) test is carried out according to ASTMD3801-2010 standard.
[0068] Aging resistance: Place the test piece in a 200°C oven for 30 days and record the mass retention rate during the aging period.
[0069] The results of the above tests on the transparent plastic toughness masterbatch prepared in Examples 1-3 and Comparative Example 1 are listed in Table 3. Table 3 is as follows:
[0070] Table 3
[0071]
[0072] By analyzing the data in Table 1, it can be learned that the transparent tough plastic masterbatches prepared in Examples 1-3 maintain high and similar effects in terms of flexural strength, tensile strength, thermal conductivity, flame retardant grade and quality retention rate, among which the flexural strength is above 95 MPa and the tensile strength is above 135 MPa, which indicates that the toughness of the three groups of transparent tough plastic masterbatches is at a high level and has excellent mechanical properties; the thermal conductivity is below 0.050, indicating that the three groups of transparent tough plastic masterbatches have good thermal insulation performance; the flame retardant grades all reach V-0, and the mass retention rates all reach 99.35% and above, indicating that the three groups of transparent tough plastic masterbatches all have excellent heat resistance, which shows that the transparent tough plastic masterbatch of the present invention has both good toughness and heat resistance.
[0073] Compared with the transparent plastic masterbatch prepared in Comparative Example 1, the transparent tough plastic masterbatch prepared in Examples 1-3 has slightly higher flexural strength and tensile strength, but significantly increased thermal conductivity, reduced flame retardancy to V-0, and reduced mass retention rate to 96.13%, which indicates that the heat-resistant PMMA in the present invention plays a decisive role in promoting the thermal insulation and heat resistance of the plastic masterbatch.
[0074] Examples 4-5 and Comparative Examples 2-3
[0075] Compared with Example 1, Examples 4-5 and Comparative Examples 2-3 differ only in that the sources of heat-resistant PMMA are different, and the other operation steps are exactly the same; the sources of heat-resistant PMMA in Example 1, Examples 4-5 and Comparative Examples 2-3 are listed in Table 4, which is as follows:
[0076] Table 4
[0077] Sources of Heat-Resistant PMMA Example 1 Preparation Example 1 Example 4 Preparation Example 2 Example 5 Preparation Example 3 Comparative Example 2 Preparation Comparative Example 1 Comparative Example 3 Preparation Comparative Example 2
[0078] Then, the transparent plastic masterbatch prepared in Examples 4-5 and Comparative Examples 2-3 was tested for performance using the same testing method as in Table 3, and the test results are listed in Table 5, which is as follows:
[0079] Table 5
[0080]
[0081] By analyzing the data in Table 5, it can be seen that the test results of the transparent tough plastics prepared in Example 1 and Examples 4-5 are not much different, while the bending strength and tensile strength of Comparative Examples 2-3 are slightly lower than those of Examples 1 and 4-5, but the thermal conductivity is significantly higher, the flame retardant grade is reduced to V-1, and the mass retention rate is reduced to below 97%, which indicates that when the usage ratio of bisphenol fluorene and bergamot lactone in the heat-resistant PMMA is X:(1-X), X should be maintained between 0.6 and 0.7.
[0082] Comparative Example 4
[0083] Compared with Example 1, the only difference is that the toughening agent prepared in Preparation Example 4 is not added, and the other operating steps are exactly the same as the steps, and finally a transparent plastic masterbatch is prepared.
[0084] Comparative Example 5
[0085] Compared with Example 1, the only difference is that the toughening agent prepared in Preparation Example 4 is replaced by a commercially available ethylene propylene toughening agent (EPR), and the other operating steps are exactly the same as the steps, and finally a transparent plastic masterbatch is prepared.
[0086] Then, the transparent plastic masterbatch prepared in Comparative Examples 4-5 was tested for performance using the same test method as in Table 3, and the test results are listed in Table 6, which is as follows:
[0087] Table 6
[0088]
[0089] By analyzing the data in Table 6, it can be seen that the thermal conductivity, flame retardant grade and mass retention rate of the transparent plastic masterbatch prepared in Comparative Examples 4-5 are at similar levels compared to those in Example 1, while the flexural strength and tensile strength are significantly reduced, which shows that the toughening agent in the transparent tough plastic masterbatch of the present invention can improve the toughness of the plastic masterbatch and enhance its mechanical properties.
[0090] The above is a detailed description of an embodiment of the present invention, but the content is only a preferred embodiment of the present invention and cannot be considered to limit the scope of implementation of the present invention. All equivalent changes and improvements made within the scope of the present invention should still fall within the scope of the patent coverage of the present invention.
Claims
1. A transparent tough plastic masterbatch, characterized in that: The raw materials include the following parts by weight: 75-85 parts of heat-resistant PMMA, 10-15 parts of toughening agent, 1-2 parts of lubricant, and 1-2 parts of antioxidant; The heat-resistant PMMA comprises PMMA, bisphenol fluorene and bergamot lactone in a molar mass ratio of 1:X:(1-X), where X=(0.5-0.7).
2. The transparent tough plastic masterbatch according to claim 1, characterized in that: The preparation method of the heat-resistant PMMA is: The first step is to add PMMA, bisphenol fluorene and bergamot lactone into the solvent according to the molar mass ratio and mix them evenly, then add the catalyst, stir at 140° C. for 4 hours, then heat to 160° C. for 1 hour, and finally heat to 200° C. for polymerization reaction for 6 hours to obtain a slurry; Step 2: Add boiling water to the slurry and stir at a constant temperature for 12 hours. After filtering and drying, dissolve in N-methylpyrrolidone and stir evenly. After filtering, dissolve in anhydrous ethanol to obtain a flocculent precipitate. Finally, wash the flocculent precipitate with ethanol several times, filter and dry to obtain heat-resistant PMMA.
3. The transparent tough plastic masterbatch according to claim 2, characterized in that: In the first step, the solvent is one of sulfolane, tetrahydrofuran and dimethylformamide.
4. The transparent tough plastic masterbatch according to claim 2, characterized in that: In the first step, the catalyst is one of anhydrous potassium carbonate, triphenylmethane and tert-butyl hydroperoxide.
5. The transparent tough plastic masterbatch according to claim 2, characterized in that: In the first step, the catalyst is used in an amount equal to the molar mass of PMMA.
6. The transparent tough plastic masterbatch according to claim 1, characterized in that: The toughening agent includes glycidyl methacrylate and vinyl acrylate in a molar mass ratio of 1:
1.
7. The transparent tough plastic masterbatch according to claim 6, characterized in that: The preparation method of the toughening agent is: The first step is to add glycidyl methacrylate and vinyl acrylate into a solvent according to the molar mass ratio and mix them evenly, then add an initiator, stir at 230° C. for 30 minutes under nitrogen protection, cool to room temperature and filter to obtain a toughening agent precursor; The second step is to distill the toughening agent precursor, and the distilled product is repeatedly washed and filtered with deionized water, and the obtained filter material is dried to obtain the toughening agent.
8. The transparent tough plastic masterbatch according to claim 1, characterized in that: The lubricant is pentaerythritol stearate.
9. The transparent tough plastic masterbatch according to claim 1, characterized in that: The antioxidant is a compound type of antioxidant 1076 or antioxidant 168.
10. A method for preparing a transparent tough plastic masterbatch as claimed in any one of claims 1 to 9, characterized in that: The method comprises the following preparation steps: S1. Weigh heat-resistant PMMA, toughening agent, lubricant and antioxidant according to weight ratio, add them into a high-speed mixer and mix them evenly to obtain a mixture; S2: placing the mixed material in an extruder and extruding it at an increasing temperature of 80-100°C at the initial temperature and 200-220°C at the final temperature, and obtaining masterbatch particles after pelletizing; S3. The obtained masterbatch particles are placed in a dryer and dried at 80° C. for 3 hours to obtain a transparent tough plastic masterbatch that can be packaged and stored.